Venture capital investing for corporate development objectives - Winters, Terry E.; Murfin, Donald L. (Journal of Business Venturing, 1988)
There is a significant new player emerging in the venture capital world whose participation is changing the way that the venture business is done. Domestic and foreign corporations have discovered that investing in venture capital adds a new dimension to their corporate development strategies and can also make an outstanding return on investment. Armed with serious amounts of cash, aware of the value of an association with their name and frequently possessing marketing power that a small company covets, corporations are competing with venture capitalists for the best deals. Obtaining a “corporate partner” is now an accepted part of a small company's financing strategy. For the corporate development executive, this activity provides a useful tool to widen the spectrum of participation in new technologies while retaining the entrepreneurial drive and reducing the cost and exposure of new ventures. However, it is not a panacea for growth and caution should be exercised to avoid creating unrealistic expectations. Both entrepreneurs and venture capitalists welcome this source of later-stage capital, providing it minimizes equity dilution and assists in product development, marketing and liquidity for their investment. However, it is a competitor for the venture capitalists in sourcing deals and a potential adversary for the entrepreneur when objectives clash. Additionally, entrepreneurs and venture capitalists often are suspicious of the corporation in the small company's boardroom. The objective of most corporations is the strategic benefits that can result from venture capital investing, such as acquisitions, technology licenses, product marketing rights, international opportunities and a window on technology. However, this objective is frequently mixed with a financial return objective and can lead to a confused strategy. Participation by corporations can take many different forms but usually begins with investments in several venture capital funds as a limited partner and evolves into direct investments in venture companies. Formation of a venture development subsidiary by the corporation is a demonstrated way to maximize the strategic rewards. If financial return is the only objective, then a stand-alone venture fund is the best vehicle. The most important factors for the strategic success of a corporate program are the creation of a high-quality deal stream and the use of outstanding people to interface between the corporation and the venture capital world. In addition, there has to be a long-term commitment, active involvement and a carefully devised internal communications strategy to promote and protect the program. Creation of a formal venture development subsidiary is probably the best way to maximize the strategic objectives. Lubrizol Enterprises operates as such a subsidiary of The Lubrizol Corporation and utilizes venture capital investing, acquisitions, partnerships, and contract research to develop strategic business units based on leading-edge technologies.